Motivators and deterrents for early career female doctors applying to surgical training programmes in the UK National Health Service: a mixed-methods study. Issue 12 (1st December 2022) - Ruparell, Kajal; Barve, Rajas; Tas, Rukiye N; Chen, Sihan; Mclaughlin, Reed; Ravendren, Andrew; Gupte, Chinmay M
Abstract : Objectives: To perform a mixed-methods study identifying motivators and deterrents to female doctors interested in core surgical training (CST). To provide tangible implementations based on the findings. Design: This study used quantitative (questionnaires) and qualitative (semistructured interviews (SSIs)) analyses. Participants completed online questionnaires on Qualtrics and SSIs were conducted remotely on Microsoft Teams. Questions were derived from previous studies and a novel term, the gender impact rating (GIR), was coined to assess the impact of gender on opportunities available during CST application. Setting: Participants were working in the UK National Health Service and data collected from December 2020 to January 2021. Participants: A total of 100 female surgical trainees in the UK ranging from Foundation Year 2 to Core Training Year 2. Main outcome measures: Participants ranked factors by their influence on their CST application. Of the 100 trainees, 21 were randomly selected for an SSI to explore their questionnaire responses. Statistical analyses were performed using MATLAB and SPSS, alongside a thematic analysis of the interviews. Results: A total of 44 out of 100 questionnaire respondents ranked early exposure to surgery as the most influential motivator, while 43% selected work-life balance as the greatest deterrent and 33% suggested mentoring schemes to encourage women to apply to CST. The median GIR was 3 out of 5, indicating a moderate perceived impact of gender on opportunities available during CST application. Qualitative analysis found four overarching themes: institutional factors (including mentorship schemes), organisational culture (including active engagement), social factors and personal factors. Conclusion: Thematic analysis suggested that seniors involving women in theatre and a supportive work environment would encourage entry of more female surgeons. Therefore, the proposed implementations are the active engagement of women in theatre and destigmatising less than full-time training. Further research into ethnicity and personality on motivations to enter surgery is advised.